2010
DOI: 10.1111/j.1539-6924.2010.01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Domain Effects and Financial Risk Attitudes

Abstract: We investigated whether financial risk preferences are dependent on the financial domain (i.e., the context) in which the risky choice options are presented. Previous studies have demonstrated that risk attitudes change when gambles are framed as gains, losses, or as insurance. Our study explores this directly by offering choices between identical gambles, framed in terms of seven financial domains. Three factors were extracted, explaining 68.6% of the variance: Factor 1 (Positive)-opportunity to win, pension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 51 publications
2
44
0
1
Order By: Relevance
“…These arguments lead to the conclusion that people may behave differently depending on the frame of the decision—gains or losses. The findings from studies presented by the authors of the Prospect theory (Kahneman and Tversky, 1979, 2000) followed by studies conducted by Kusev et al (2009, 2011) and Vlaev et al (2010), support the hypothesis that decisions under risk may vary depending on the frame of the decision: framed as either loss or gain.…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…These arguments lead to the conclusion that people may behave differently depending on the frame of the decision—gains or losses. The findings from studies presented by the authors of the Prospect theory (Kahneman and Tversky, 1979, 2000) followed by studies conducted by Kusev et al (2009, 2011) and Vlaev et al (2010), support the hypothesis that decisions under risk may vary depending on the frame of the decision: framed as either loss or gain.…”
Section: Introductionmentioning
confidence: 73%
“…Furthermore, Kusev et al (2009) provided evidence that variation in the content of decisions leads to variation in financial risk preferences. Moreover, Vlaev et al (2010) postulated that risk preferences may differ depending on the decision domain because the reference point may be different for various domains, for instance, monetary gambling vs. insurance. Vlaev et al (2010) conducted a study in which they distinguished between monetary gambles, hazard losses, investment, insurance, pension provision, job salary change, and mortgage buying.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in a review of financial risk preferences and financial management areas (i.e. financial domains), Vlaev et al determined that women are relatively more risk-averse than men [10]. Similarly, in a questionnaire-based study of Turkish financial advisers, Tutek et al noted that female financial advisers, at the same risk level, could offer more valuable advice on controlling risk because women are more risk-averse [8].…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Dohmen et al (forthcoming) show that the parents' self-reported risk attitude in a specific domain best explains the child's attitude in that domain. However, even within domains differences might arise (Vlaev et al 2010). For instance, an individual might be willing to take income risk but not health risk to proceed in her career.…”
Section: Literature Reviewmentioning
confidence: 99%